Pengaruh kredibilitas merek terhadap word of mouth melalui customer satisfaction dan customer loyalty pada Mirota Kampus Yogyakarta - Syarkani, Yofi; Cakranegara, Pandu Adi; Ronaldo, Reza; Ahmaddien, Iskandar (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2022)
The development of the retail business has become very competitive due to offline and online competition. Business owners must provide the best service to customers because the dynamic behavior of customers encourages them to try other brands if their needs are not met. Because the number of competitors continues to increase and companies must have a good positioning and power to retain their customers and provide a positive word of mouth. The purpose of this study was to determine the effect of Brand Credibility on Word of Mouth through Customers and Customer Loyalty as Intervening at Mirota, Yogyakarta Campus. The design of this research is a causal study using hypotheses. The sampling technique used in this research is non-probability purposive sampling. The analysis technique uses Partial Least Square (PLS) - Structural Equation Modeling (SEM). Respondents were taken from 230 customers of Mirota Yogyakarta Campus in Yogyakarta with certain characteristics. The results show that Customer and Customer Loyalty is an intervention between Word of Mouth Brand Credibility, there is an effect of Brand Credibility on Customer goals and Customer Loyalty, there is an influence of Customer and Customer Loyalty on Word of Mouth, and there is an influence of Customer and Customer Loyalty on Word of Mouth. . Other results show that there is an influence of Customers on Customer Loyalty.